Construction of schools in Iraq during Seljuk era (449-590 / 1055-1194) - Farman Bayeez Ameen; Rabeha Fatah Shehk Mohamad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
important aspets of cunstrtion in Islamic civilisation.Generaly saljuks were very interested in buildng schools.Iraq became spiritual life of muslims because it was the center of Abassid chaliphate.caliphs,sultans,ministters,scientist and women of high ststure had a pivotal role in building and developing schools Efforts of each of the above mentioned expressed Islamic sects Nizam al mulk, the yread vizier of saljuks, played an important and effective role in building schools, and he also asked people to build more schools. The pluralism different religlous scholars and administrators about schools led to the influx of students and teachers from all over the islamic world to Iraq especially to Baghdad city since it used to be the center of science .